A Clinicopathological Study of Nasal, Paranasal Sinus, and Nasopharyngeal Lesions. - Zahraa Hasan (مجلة الكوفة الطبية)
Background: The nasal cavity, nasopharyngeal, and paranasal areas are affected by several non -neoplastic and neoplastic disorders. Determining whether the lesion is neoplastic or non-neoplastic is challenging. Therefore, histopathological analysis is crucial for both the pathologists and surgeons. Objective: This research aimed to assess the pathological analysis of the diseases occurring in the nasal cavity, paranasal sinuses, and nasopharyngeal area according to their frequency, age, sex, and distribution by site Methods: The current study with cross-sectional design was performed in the histopathological department of Shahid Ghazi Al-Harery Teaching Surgical Hospital in Baghdad Medical City over a three-year period from December 2021 to December 2024. Tissue samples were collected and fixed in 10% neutral-buffered formalin. The material was processed as routine. Five-micron-thick sections were cut and stained with hematoxylin and eosin. Results: Among 299 patients, 96 were females and 203 were males. The majority of the affected age group in this study was from the 2nd decade to the 4th decade. Among 299 cases; 169 were non-neoplastic lesion cases and 130 neoplastic lesion cases of which 60 were benign and 70 were malignant. Out of 169 cases of inflammatory and non-neoplastic lesions, inflammatory nasal polyp (81 cases) was the most common lesion. Out of 60 benign neoplastic cases, sinonasal papilloma (24 cases) was the most common benign neoplastic lesion. Out of 70 malignant cases, nasopharyngeal carcinoma was the commonest histopathological type, constituting 35 cases.  Conclusion: Since the majority of nasal cavity, paranasal sinus, and nasopharyngeal lesions can appear as polyp-like lesions; a histopathological analysis of these lesions can assist surgeons in diagnosing a condition and choosing the best course of therapy for the patient.